Dendritic cell vaccines in the treatment of multiple myeloma: advances and limitations - Büchler, Tomas; Hajek, Roman (Medical oncology (Northwood, London, England), 2002)
Dendritic cells (DCs) are antigen-presenting cells that play a key role in the induction of cytotoxic T-lymphocytes. Adjuvant immunotherapy with antigen-loaded DCs represents an attractive anticancer strategy for multiple myeloma (MM). Autologous DCs loaded with idiotypic protein or other myeloma-associated antigen have been used in several clinical trials. Preclinical and first clinical experience have provided valuable insights in the mechanisms of cellular immunity, but few, if any, patients with MM benefited from such vaccination. Taken together, the data suggest that antitumor T-cell responses fail in MM because of a deregulated cytokine network, downregulation of costimulatory surface receptor expression, and changes in T-cell repertoire, enabling tumor cells to escape immune effectors by preventing the antitumor immune response. We discuss current clinical protocols for DC-based immunotherapy in MM and review some strategies that may increase the efficacy of DC vaccines.
Keywords: klinické zkoušky jako téma; Dendritic Cells; Clinical Trials as Topic; mnohočetný myelom; Cancer Vaccines; dendritické buňky; Vaccination; Humans; vakcinace; Multiple Myeloma; protinádorové vakcíny; lidé